Pancasila dan Pemilihan Umum - ningtyas, mufida putri (Maliki Interdisciplinary Journal, 2025)
Pancasila serves as a fundamental cornerstone in conducting elections in Indonesia, Upholding the values of Belief in the One and Only God, Just and Civilized Huanity, the Unity of Indonesia, Democracy Guided by the Inner Wisdom of Deliberations Among Representatives, and Social Justice for All Indonesians. This study aims to explore the role of Pancasila as a normative and operational guideline in achieving honest, fair, and democratic elections. However, various challenges arise in its implementation, including low legal awareness, societal welfare issues, and the exploitation of identitiy politics, which often hinder substantive democracy. This study recommends strategic measures such as enhancing political education, strengthening, electoral integrity, and simplifying the electoral system to ensure elections align with Pancasila values.